The design of the computer-telephony integration system for small and medium industries - Embong, Abdullah; Osman, Azam; Samsudin, Azman; Zulhamiros, Mohd; Jamaludin, Zulikha (2000)
The objective of this paper is to describe a project on designing and developing a computer-telephony integration (CTI) system for small medium industries (SMI). This project explores a huge research area in CTI technologies. CTI research area such as computer, telephone network, standards, distributed multimedia elements, and voice processing are core technologies, which are studied and evaluated in order to design a low-cost CTI system for SMI. A CTI system was developed using GlobalCall API approach. This system, called IK-TIKS, aims to support some degree of distributed multimedia applications in the form of CTI services for SMIs in the northern region of Malaysia. IK-TIKS, a powerful blend between telephones and computers, is a system developed in the hunt for boosting SMIs’ income and productivity. With IK-TIKS, business activities can be done at effective cost, which directly encourage in boosting a company’s productivity.